Serum C-reactive protein test in diagnosis of septic complications of cerebrospinal fluid shunts for hydrocephalus. - Bayston, R (1979)
Serial tests for serum C-reactive protein (CRP) were carried out on 40 children undergoing cerebrospinal fluid shunt surgery, to determine the pattern of appearance and disappearance of CRP in relation to this type of operation, in the absence of postoperative complications. Samples of sera from a further 268 children, 79 of whom presented after shunt surgery with symptoms suggesting infective complications related to the shunt, were examined for CRP. The results showed that, while the test in negative in uncomplicated colonisation of ventriculo-atrial shunts, it is reliably positive in patients with colonised ventriculo-peritoneal shunts, ventriculitis, or shunt nephritis.